Industria, importacion y comercializacion de plaguicidas en Costa Rica - Bernal, J.A.=700 1 Hidalgo, C.; Garcia, J.E.
(Es, En)
Ilus., 54 ref.
Keywords: PLAGUICIDAS; INDUSTRIA; IMPORTACIONES; MERCADEO; COSTA RICA